2007
DOI: 10.1038/sj.onc.1210981
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D3 action in androgen receptor regulation and prostate cancer

Abstract: Prostate cancer (PCa) cell proliferation is dependent on activation of the androgen receptor (AR), a liganddependent transcription factor. AR activation controls G1-S phase progression through fostering enhanced translation of the D-type cyclins, which promote cell cycle progression through activation of CDK4/6. However, the D-type cyclins harbor additional, CDK4/6 kinase-independent, functions through manipulation of transcription factors, including AR. It was previously established that cyclins D1 and D3 hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 66 publications
1
20
0
Order By: Relevance
“…AR activity is modulated by different signal-transduction pathways (Reddy et al, 2006), by cyclins (Olshavsky et al, 2008), by interaction with numerous co-activators and repressors (Heemers and Tindall, 2007) and by diverse posttranslational modifications, including the covalent conjugation of the small ubiquitin-like protein, SUMO-1 (Callewaert et al, 2004). In addition, mutations preferentially occurring in the ligand-binding domain of AR in advanced PCa modify ligand specificity, thereby decreasing the dependence on androgens for the stimulation of proliferation (Taplin and Balk, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…AR activity is modulated by different signal-transduction pathways (Reddy et al, 2006), by cyclins (Olshavsky et al, 2008), by interaction with numerous co-activators and repressors (Heemers and Tindall, 2007) and by diverse posttranslational modifications, including the covalent conjugation of the small ubiquitin-like protein, SUMO-1 (Callewaert et al, 2004). In addition, mutations preferentially occurring in the ligand-binding domain of AR in advanced PCa modify ligand specificity, thereby decreasing the dependence on androgens for the stimulation of proliferation (Taplin and Balk, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…23 Cyclin D3 is also linked to attenuation of the ligand-dependent proliferation-promoting function of AR in AR-dependent prostate cancer cells. 18 Zong et al demonstrated a potential CDK4-independent mechanism for cyclin D3-mediated repression of both AR-dependent transcriptional activity and AR-dependent proliferation, whereby a cyclin D3/AR complex that also incorporates CDK11p58 induces AR phosphorylation at Ser-308. 39,40 We found that in contrast to cyclin D3 expression, the downregulation of caspase-2 expression inhibits AR activity in LNCaP cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Olshavsky et al 18 found that cyclin D3 immunoprecipitates with AR in prostate cancer cells. Cyclin D3 inhibits AR activity by modulating ligand-dependent conformational changes and chromatin binding activity.…”
Section: Ar-cyclin D3 Interaction Depends On Caspase-2mentioning
confidence: 99%
See 2 more Smart Citations